Static voltage stability analysis of integrated smart energy systems - Huang, Jungao; Ding, Xuetian; Jin, Dongyong; Liu, Zhangjie (Frontiers in Energy Research, 2024)
The analysis of multi-energy flows forms the cornerstone for the study of state estimation, safety assessment, and optimization in integrated smart energy systems (ISES). The interactions between various energy flows and the inherent variability of renewable energy sources often lead to significant challenges to the static stability of ISES. This paper investigates the static voltage stability of ISES under multi-energy coupling conditions through multi-energy flow analysis in electric-gas-thermal energy systems. First, a steady-state model of the ISES is constructed by representing the interconnected energy subsystems as equivalent sources and loads in the power grid. Subsequently, through the coupling elements of ISES, the power flows of the natural gas system (NGS) and the district heating system (DHS) are converted into active power in the electrical power system(EPS), resulting in an equivalent power flow equation for the ISES. Then, using Brouwer's fixed-point theorem, the analytical sufficient conditions for solving the equivalent power flow equation are derived. Finally, a simulation model based on MATLAB/Simulink is established, and the simulation results verify the correctness and effectiveness of the proposed conclusions.